Implementasi Fungsi Protokoler Sekretariat Daerah Dalam Mendukung Kelancaran Agenda Pimpinan Daerah - Aloysius Alfianto Elang; Intan Mustafa; Markus Retu (Jompa Research and Development, 2026)
This study aims to analyze the implementation of protocol functions within the Regional Secretariat in supporting the smooth execution of regional leaders’ agendas from a communication studies perspective using a Public Relations approach. Protocol functions play a strategic role in managing formal communication, event arrangements, and institutional relations that directly influence the image and authority of regional leaders. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation of protocol activities and relevant stakeholders. Data analysis was conducted descriptively using George C. Edwards III’s Policy Implementation Theory, which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. The findings indicate that the protocol functions of the Regional Secretariat have been systematically implemented to support the effectiveness of leadership agendas, particularly through well-coordinated communication and structured event management. However, challenges remain in terms of resource availability and inter-unit coordination, which affect the optimization of protocol implementation. This study concludes that protocol functions extend beyond administrative duties and represent a strategic Public Relations practice that contributes to building the image, credibility, and public legitimacy of regional leaders.